Several comments on Czechoslovak motives in the work of Pablo Neruda - Goldstein, Klara (Bohemica Olomucensia, 2017)
This text attempts to describe and analyse motives connected with Czechoslovakia, especially touches Neruda's poem The Prague Interview, which is dedicated to Prague and Julius Fucik and through an analysis and comparison it shows how differently was an icon of the Czechoslovakian communism seen by Neruda and by the young communist poets in the Czechoslovakia. Also focuses on other Neruda's poems about Prague or Czechoslovakia that appear in his work.
Keywords: Pablo Neruda; Julius Fucik; liberation struggle; socialist realism